Single Atom Ruthenium‐Doped CoP/CDs Nanosheets via Splicing of Carbon‐Dots for Robust Hydrogen Production - Song, Haoqiang; Wu, Min; Tang, Zhiyong; Tse, John S.; Yang, Bai; Lu, Siyu (Angewandte Chemie International Edition, 2021)
Ultrathin two‐dimensional catalysts are attracting attention in the field of electrocatalytic hydrogen evolution. This work describe a composite material design in which CoP nanoparticles doped with Ru single‐atom sites supported on carbon dots (CDs) single‐layer nanosheets formed by splicing CDs (Ru1CoP/CDs). Small CD fragments bore abundant functional groups, analogous to pieces of a jigsaw puzzle, and could provide a high density of binding sites to immobilize Ru1CoP. The single‐particle‐thick nanosheets formed by splicing CDs acted as supports, which improved the conductivity of the electrocatalyst and the stability of the catalyst during operation. The Ru1CoP/CDs formed from doping atomic Ru dispersed on CoP showed very high efficiency for the hydrogen evolution reaction (HER) over a wide pH range. The catalyst prepared under optimized conditions displayed outstanding stability and activity: the overpotential for the HER at a current density of 10 mA cm−2 was as low as 51 and 49 mV under alkaline and acidic conditions, respectively. Density functional theory calculations showed that the substituted Ru single atoms lowered the proton‐coupled electron transfer energy barrier and promoted H−H bond formation, thereby enhancing catalytic performance for the HER. The findings open a new avenue for developing carbon‐based hybridization materials with integrated electrocatalytic performance for water splitting. A composite material was synthesized in which CoP nanoparticles, doped with single‐atom Ru sites, are supported on single‐particle thick nanosheets formed by splicing of CDs (Ru1CoP/CDs). The catalyst prepared under optimized conditions displayed an outstanding stability and activity for hydrogen evolution reaction in alkaline and acidic conditions.